Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/0284185114533683
|View full text |Cite
|
Sign up to set email alerts
|

Submilisievert ultralow-dose CT colonography using iterative reconstruction technique: a feasibility study

Abstract: This pilot study shows that iterative reconstruction technique is a feasible method to decrease the radiation dose from CT colonography for both positions below 1mSv. Further investigations of larger scale need to be done to clarify, whether such a low radiation dose would influence the detection of polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…Gryspeedt et al used a structure preserving diffusion de-noising method in 31 patients scanned with a sub-mSv technique and found this reduced noise and improved signal to noise ratios compared to sub-mSv images reconstructed without this technique [17]. Lambert et al also pushed the dose into the sub-mSv range in 16 patients using a hybrid iterative reconstruction technique and found that all segments were rated as evaluable on the low dose series reconstructed with iterative reconstruction [18]. However, no polyp assessment was performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Gryspeedt et al used a structure preserving diffusion de-noising method in 31 patients scanned with a sub-mSv technique and found this reduced noise and improved signal to noise ratios compared to sub-mSv images reconstructed without this technique [17]. Lambert et al also pushed the dose into the sub-mSv range in 16 patients using a hybrid iterative reconstruction technique and found that all segments were rated as evaluable on the low dose series reconstructed with iterative reconstruction [18]. However, no polyp assessment was performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The technical performance of an imaging test can be measured directly. Image quality at different dose levels can be compared among different CT scanners using basic phantom modules for the assessment of low-contrast and high-contrast resolution, spatial resolution or by its evaluation by independent observers (25, 26). However, to test the diagnostic performance, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Both readers were allowed to change the densityrendering threshold (below which a voxel becomes transparent and represents intraluminal gas) to adjust the appearance of the endoluminal view. 12 Each colonic segment was evaluated in axial thin sections and 900/100-HU window setting for image quality on the same five-point Likert scale. Endoluminal density and noise expressed as standard deviation was measured in an airfilled lumen in a circular region of interest of approximately 200 mm 2 in each colonic segment.…”
Section: Methodsmentioning
confidence: 99%
“…Difficulty of constructing the fly path, which is mostly calculated automatically but has to be reworked manually in some cases, was expressed on a fivepoint scale (1, automatic; 5, impossible), and the number of computer-aided detection (CAD) strikes was recorded. 12 …”
Section: Methodsmentioning
confidence: 99%